Testing William Baumol's "Toward a Newer Economics: The Future Lies Ahead!" - Marco Piatti; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2010)
20 years ago, William Baumol provided an interesting wish list that outlined his hopes for the future of economics over the next hundred years. Impatiently, this paper puts his wish list to the test by comparing the characteristics of publications that appeared in the American Economic Review before Baumol's contribution in 1991 (1984 to 1988) and those published 20 years later (2004 to 2008), and by looking at the Job Openings for Economists between 1991 and 2009. Focusing on issues such as the role of mathematics, the short-run orientation of macroeconomics, the emphasis of economic history versus the history of economic ideas, as well as a more concrete menu of wishes for applied economics, we observe that this was not just a wish list, but is in many ways a list that offers an accurate picture of what has changed over time and what has happened in recent years.
Keywords: B41; A20; A10; 330; American Economic Review; William Baumol; Mathematics; Macroeconomics; Applied Economics; Job Openings